Preparation method of small-size defect cerium-based MOFs supported metal catalyst for hydrogenation

By preparing small-size defective cerium-based MOFs-supported metal nanoparticle composite catalytic material, the problems of existing catalysts being easily lost, toxic and costly in DCPD hydrogenation reaction are solved, and efficient, stable and low-cost catalytic effect is achieved.

CN119524926APending Publication Date: 2025-02-28UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411670471.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing precious metal catalysts are easily lost, toxic and costly in DCPD hydrogenation reaction. Non-precious metal catalysts such as Rainie Nickel cannot achieve cyclic catalysis due to poor stability, making it difficult to develop efficient, stable and low-cost catalysts.

Method used

By preparing a composite catalytic material of small-size defective cerium-based MOFs-supported metal nanoparticles, the size and defects of the MOFs support are adjusted by using a monocarboxylic acid regulator, and the structure and load of metal nanoparticles are optimized in combination with the reduction reaction conditions to achieve efficient utilization of metal active components.

Benefits of technology

It achieves efficient catalytic DCPD hydrogenation performance, improves the stability and recycling ability of the catalyst, reduces the amount of metal used, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524926A_ABST
    Figure CN119524926A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a small-size defective cerium-based MOFs supported metal catalyst for hydrogenation, and belongs to a preparation technology of a nano composite catalytic material. The preparation method comprises the following steps: in a cerium-based MOFs synthesis process, introducing a proper amount of monocarboxylic acid as a regulator to synthesize a cerium-based MOFs carrier with adjustable defects and size, then loading a metal active component to the cerium-based MOFs carrier, and combining adjustment of reduction conditions to prepare the cerium-based MOFs loaded metal composite catalyst with small-size defects for DCPD hydrogenation. The defects and the size of the cerium-based MOFs carrier are effectively regulated and controlled through the monocarboxylic acid regulator, controllable regulation of the electronic state, the size and the catalytic activity of the loaded metal active component can be achieved by combining regulation and control of the reduction condition of the loaded metal nanoparticle active component, the process is simple, parameters are controllable, the period is short, and the method is suitable for DCPD hydrogenation large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano-composite catalytic material preparation technology and dicyclopentadiene (DCPD) hydrogenation application, and specifically relates to a method for preparing a small-size defect cerium-based metal organic framework (MOFs)-loaded metal nanoparticle composite catalytic material. Background Art

[0002] High energy density fuel is the power guarantee of hypersonic aircraft and has always attracted global attention. Exo-THDCPD has the advantages of high density (0.939 g / cm3), low freezing point (-79 ℃), high combustion calorific value (39.6MJ / Kg), etc. It is currently the best high energy density liquid hydrocarbon fuel with comprehensive performance. Its synthesis and preparation technology is the focus of competition among countries. Exo-THDCPD was first developed by the United States and gradually became the standard fuel for its Air Force and Navy. my country's research in this field started relatively late, and it is urgent to develop independent synthesis technology for high-quality aerospace fuels. Dicyclopentadiene (DCPD) can be hydrogenated to produce a three-ring structure of endo-THDCPD, which can be further isomerized to produce exo-THDCPD. Therefore, it is crucial to achieve efficient catalytic hydrogenation of DCPD. Currently, for olefin hydrogenation catalysts, supported precious metal catalysts represented by Pd / C, Pd / Al2O3, Ru / SBA-15, etc. are mainly capable of efficiently cracking H2 and moderately adsorbing DCPD; however, the easy loss and poisoning of precious metals and the high cost restrict their practical application. Raney nickel, as a non-precious metal catalyst, has good catalytic ability, but due to its poor stability, it cannot achieve cyclic catalysis. Therefore, it is crucial and challenging to develop new synthetic strategies to prepare supported catalysts with high DCPD hydrogenation activity, high stability and low metal loading.

[0003] Metal-organic frameworks (MOFs) are a new class of periodic porous materials with the characteristics of adjustable structure, high porosity, large specific surface area, and ordered framework structure, showing potential application prospects in many fields. In particular, cerium-based MOFs materials have shown unique advantages in the field of catalysis due to the unique 4f5d electronic structure of Ce elements. Loading metal active components into the framework of cerium-based MOFs can improve the atomic utilization of metal components, adjust the dispersion, stability and electron density of catalytic active sites, and further synergistically enhance the catalytic performance. In addition, the DCPD molecule has a large dynamic diameter, and small-sized catalysts are conducive to enhancing the mass transfer and adsorption of large-sized DCPD substrate molecules, accelerating the DCPD reaction process. Adjusting the cerium-based MOFs carrier and sample synthesis preparation conditions can affect the structure of the cerium-based MOFs carrier, further optimize the heterogeneous structure and chemical properties of the carrier and metal components, enhance the unique interaction between the metal active components and the cerium-based MOFs heterogeneous interface, and optimize the electronic structure and abundance of the loaded metal active sites, which is expected to achieve efficient catalytic DCPD hydrogenation performance.

[0004] Therefore, how to prepare cerium-based MOFs-loaded metal composite catalytic materials with adjustable size and defects with low cost, high activity and high stability is an urgent need for the efficient development of catalytic materials for dicyclopentadiene hydrogenation. Summary of the invention

[0005] The purpose of the present invention is to develop a method for preparing a composite catalytic material of cerium-based MOFs-loaded metal nanoparticles with simple process and controllable parameters by preparing a cerium-based MOFs carrier with adjustable size and defects and adjusting the reduction reaction conditions of the carrier-loaded metal active components, so as to achieve efficient catalytic DCPD hydrogenation performance.

[0006] The preparation steps of the present invention are:

[0007] 1) preparing a mixed solution of an organic ligand, a soluble cerium salt, and a monocarboxylic acid regulator, reacting the mixture by a solvothermal method, centrifuging, washing, and drying the obtained product, and synthesizing a cerium-based MOFs carrier with adjustable defect content and size, wherein the molar ratio of the cerium salt to the monocarboxylic acid regulator in the mixed solution is 1:0.01-100, that is, the monocarboxylic acid regulator added is 0.01-100 molar equivalents (0.01-100 eq) relative to the cerium salt;

[0008] 2) Prepare a metal salt solution with a metal ion concentration of 0.01-10 g / L at room temperature; first, uniformly disperse the cerium-based MOFs carrier in a solvent at 25-100 °C, wherein the content of the cerium-based MOFs carrier in the solvent is 0.1-500 g / L, and add the prepared metal salt solution under stirring conditions to obtain a mixed solution, so as to promote the adsorption of metal ions into the cerium-based MOFs carrier framework, and the metal loading amount relative to the carrier is 0.01-20 wt%;

[0009] 3) Adding the reducing agent solution to the mixed solution of step 2), the molar ratio of the reducing agent added to the metal ions in the added metal salt solution is 50~0.1:1, stirring the reaction at 25~100°C for 1~48 hours, and then centrifuging, washing and drying the product in sequence to obtain a cerium-based MOFs-loaded metal nanoparticle composite catalyst with adjustable size and defects.

[0010] Furthermore, the solvothermal method described in step 1) is to add an organic ligand to N,N-dimethylformamide (DMF) with a ligand solution concentration of 0.01~1 mol / L, stir at room temperature to completely dissolve the organic ligand to obtain a clear solution A; add a cerium salt and a certain amount of a monocarboxylic acid regulator to deionized water, stir at room temperature to mix the solution evenly, and obtain a clear and transparent solution B; mix solution A and solution B in a volume ratio of 0.01~1:0.01~1, and stir and react at 25~150°C for 15 min~72 h.

[0011] Furthermore, the cerium salt in step 1) includes one of ammonium cerium nitrate and cerium nitrate.

[0012] Further, the monocarboxylic acid regulator in step 1) includes one of formic acid, acetic acid, trifluoroacetic acid, benzoic acid, butyric acid, caprylic acid, capric acid, and lauric acid;

[0013] The organic ligand described in step 1) includes one of terephthalic acid, 2-aminoterephthalic acid, 2-nitroterephthalic acid, 2-bromoterephthalic acid, 2-fluoroterephthalic acid, 2-sulfonateterephthalic acid, 2-hydroxyterephthalic acid, 2,5-dihydroxyterephthalic acid, 2,5-dichlorobenzaldehyde, 2,5-pyrazinedicarboxylic acid, 2,5-pyridinedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, 2,2'-bipyridine-5,5'-dicarboxylic acid, and trimesic acid;

[0014] The metal salt in step 2) includes one of nickel nitrate, cobalt nitrate, copper nitrate, iron nitrate, zinc nitrate, platinum nitrate, palladium nitrate, nickel chloride, cobalt chloride, copper chloride, iron chloride, zinc chloride, ruthenium chloride, platinum chloride, and palladium chloride;

[0015] The solvent of the metal salt solution in step 2) includes one of deionized water, methanol, and ethanol; the solvent for carrier dispersion in step 2) includes one of deionized water, deionized water + n-hexane, methanol, and ethanol;

[0016] The reducing agent in step 3) includes one of sodium borohydride, tetrabutylamine borane, and hydrazine hydrate; the solvent for dissolving the reducing agent in step 3) includes one of deionized water, methanol, and ethanol.

[0017] Preferably, the monocarboxylic acid regulator in step 1) is formic acid; the organic ligand in step 1) is terephthalic acid; the metal salt in step 2) is nickel nitrate; the solvent of the metal salt solution in step 2) is methanol; the solvent for dispersing the carrier in step 2) is methanol; the reducing agent in step 3) is sodium borohydride; and the solvent for dissolving the reducing agent in step 3) is methanol.

[0018] Furthermore, the stirring time at room temperature in step 1) is 5 min to 1 h.

[0019] Furthermore, in step 2), the stirring time is 1 to 48 h.

[0020] Furthermore, the reducing agent solution in step 3) has a concentration of 0.01-10 mol / L.

[0021] Furthermore, the drying in step 1) and step 3) is performed by placing the product in a vacuum oven at 60-150° C. for 4-48 h.

[0022] The present invention adjusts the size and defects of the cerium-based MOFs carrier by regulating the amount of the introduced monocarboxylic acid regulator, combines the regulation of the reduction conditions of the metal nanoparticles, synergistically optimizes the structure of the active metal component, prepares a small-size defect cerium-based MOFs-loaded metal nanoparticle composite catalytic material, and achieves efficient catalytic DCPD hydrogenation performance.

[0023] In the synthesis process of cerium-based MOFs, the present invention effectively regulates the growth kinetics and defect content of cerium-based MOFs by adjusting the amount of monocarboxylic acid additive introduced and utilizing the competitive coordination effect between the monocarboxylic acid regulator and the organic ligand with the Ce-oxo cluster. The carrier size and defect content are regulated to enhance the carrier-metal strong interaction between the carrier and metal nanoparticles, thereby effectively optimizing the electronic structure and active site distribution of the metal nanoparticles.

[0024] The present invention adjusts the loading amount, dispersion and electronic state of metal nanoparticles by changing the reduction conditions such as the amount of reducing agent added, the type of reducing solvent, and the amount of metal ion solution added during the metal nanoparticle loading process, and also affects the Ce3+ / Ce4+ ratio and the carrier stability in the MOFs carrier, changes the carrier-metal strong interaction between the MOFs carrier and the metal nanoparticles, synergistically regulates the electronic structure of the metal nanoparticles and the number of exposed metallic active sites, enhances the effective adsorption and activation of the metal active sites on H2 and the C=C double bond in DCPD, and realizes the effective regulation of the DCPD hydrogenation performance and cycle stability of the cerium-based MOFs-supported catalyst.

[0025] The advantages of the present invention are:

[0026] 1) Developed a small-size defect cerium-based MOFs-loaded metal composite catalytic material for catalytic DCPD hydrogenation for the first time;

[0027] 2) Monocarboxylic acid regulators can effectively regulate the defects and size of cerium-based MOFs carriers. Combined with the regulation of the reaction conditions for reducing metal active components, the electronic state, size and catalytic activity of the loaded metal active components can be controlled.

[0028] 3) The preparation method has simple process, controllable parameters and short cycle, and is suitable for large-scale production of DCPD hydrogenation. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope photograph of the U(Ce)-40eq carrier with small defects obtained in Example 1.

[0030] Figure 2 This is a transmission electron microscope photograph of the small-size defect UiO-66(Ce) loaded Ni nanoparticles (Ni5@U(Ce)-40eq) composite catalytic material obtained in Example 1.

[0031] Figure 3 This is the XRD pattern of the small-size defect UiO-66(Ce) loaded Ni nanoparticles (Ni5@U(Ce)-40eq) composite catalytic material obtained in Example 1. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below in conjunction with specific implementation methods.

[0033] Example 1

[0034] First, 1 g of terephthalic acid (BDC) was added to 30 mL of DMF and stirred at room temperature for 10 min to obtain solution A. 3.65 g of ammonium cerium nitrate and 10 mL of anhydrous formic acid regulator (40 eq) were added to 12.5 mL of deionized water and stirred at room temperature for 10 min to obtain solution B. Solution A and solution B were mixed and stirred in a 100 °C oil bath for 15 min. After the reaction, the product was centrifuged, washed, and dried in a 100 °C vacuum oven for 12 h to prepare a UiO-66(Ce) carrier with small size defects, recorded as U(Ce)-40eq. Then, at room temperature (25 °C), 100 mg of U(Ce)-40eq carrier was evenly dispersed in 10 mL of methanol solution, and 5 mL of prepared nickel nitrate methanol solution (1g / L Ni2+) was added. After the mixed solution was stirred for 6 h, 5 ml of prepared methanol solution containing 16.11 mg of sodium borohydride was added. The molar ratio of metal ions in the sodium borohydride and nickel nitrate methanol solution was 5:1. The reaction was stirred at room temperature for 1 h. The product was centrifuged, washed, and vacuum dried at 80 °C for 12 h to obtain a small-size defective U(Ce)-40eq loaded with 5 wt% Ni nanoparticles composite catalytic material, recorded as Ni5@U(Ce)-40eq. Figure 1 Scanning electron microscope (SEM) images show that the prepared U(Ce)-40eq particles are very small, with an average particle size of about 70nm. Figure 2 Transmission electron microscopy (TEM) images show that Ni nanoparticles are uniformly loaded on the U(Ce)-40eq carrier without obvious agglomeration, and the average particle size of Ni nanoparticles is about 2 nm. In addition, the X-ray diffraction (XRD) pattern ( Figure 3 ) It can be seen that the Ni5@U(Ce)-40eq composite material has obvious diffraction peaks at 2θ = 7.1°, 8.2°, 24.8°, 29.7°, 41.8°, etc., which belong to the UiO-66(Ce) crystal phase, indicating that the typical UiO-66(Ce) crystal structure of the carrier is not destroyed after loading Ni nanoparticles and has high stability. In addition, no diffraction peak of Ni / NiO is observed in the XRD spectrum, indicating that the Ni nanoparticles are small in size and highly dispersed.

[0035] DCPD hydrogenation performance and cycle stability test: 0.01 g of powdered catalyst was weighed and added to a high-pressure hydrogenation reactor, 5 mL of methanol solvent and 100 μL of DCPD substrate were added, the reactor was sealed, and the entire device was repeatedly purged with H2 to remove air. Then, the reactor H2 reaction pressure was set to 2 MPa, the reaction temperature was 70 ℃, the reaction time was 90 min, and the stirring speed was 600 rpm. After the catalytic reaction was completed, the catalyst and solvent were centrifuged and separated. The supernatant was diluted with methanol solvent and the product components were analyzed by GC-MS liquid chromatography-mass spectrometry. The DCPD conversion rate was 100% and the THDCPD selectivity was >99.9%. The centrifuged catalyst was centrifuged and washed 3 times with methanol and then transferred to a high-pressure hydrogenation reactor. The above steps were repeated. After 5 catalytic cycle tests, the DCPD conversion rate was 100% and the THDCPD selectivity was 96.1%.

[0036] Example 2

[0037] First, 1.11 g of 2,5-pyridinedicarboxylic acid (PDB) was added to 30 mL of DMF and stirred at room temperature for 1 h to obtain solution A. 2.89 g of Ce(NO3)3·6H2O and 7.5 mL of anhydrous acetic acid regulator (30 eq) were added to 12.5 mL of deionized water and stirred at room temperature for 1 h to obtain solution B. Subsequently, solution A and solution B were mixed and stirred at 25 °C for 12 h. After the reaction, the product was centrifuged, washed and dried in a vacuum oven at 100 °C for 24 h to prepare a small-size defective Ce-MOFs-PDB carrier, recorded as Ce-PDB-30eq. Then, 200 mg Ce-PDB-30eq carrier was uniformly dispersed in 30 mL of deionized water solution at 60 °C, and 3 mL of freshly prepared nickel nitrate aqueous solution (4 g / L Ni2+) was added. After the mixed solution was stirred for 1 h, 2.5 ml of freshly prepared deionized water solution containing 77.32 mg of sodium borohydride was added. The molar ratio of metal ions in the methanol solution of sodium borohydride and nickel nitrate was about 10:1. The reaction was stirred at 60 °C for 12 h. After centrifugation, washing, and vacuum drying at 80 °C for 24 h, the defective Ce-PDB-30eq loaded with 6 wt% Ni nanoparticles composite catalytic material was obtained, which was recorded as Ni6@Ce-PDB-30eq.

[0038] DCPD hydrogenation performance and cycle stability test: 0.01 g of powdered catalyst was weighed and added to a high-pressure hydrogenation reactor, 5 mL of methanol solvent and 100 μL of DCPD substrate were added, the reactor was sealed, and the entire device was repeatedly purged with H2 to remove air. Then, the reactor H2 reaction pressure was set to 2 MPa, the reaction temperature was 70 ℃, the reaction time was 90 min, and the stirring speed was 600 rpm. After the catalytic reaction was completed, the catalyst and solvent were centrifuged and separated. The supernatant was diluted with methanol solvent and the product components were analyzed by GC-MS liquid chromatography-mass spectrometry. The DCPD conversion rate was 100% and the THDCPD selectivity was >99.9%. The centrifuged catalyst was centrifuged and washed 3 times with methanol and then transferred to a high-pressure hydrogenation reactor. The above steps were repeated. After 5 catalytic cycle tests, the DCPD conversion rate was 98.63% and the THDCPD selectivity was 97.4%.

[0039] Example 3

[0040] First, 1.64 g of 2-sulfonated terephthalic acid (BDC-SO3) was added to 30 mL of DMF and stirred at room temperature for 30 min to obtain solution A. 3.65 g of ammonium cerium nitrate and 2.5 mL of trifluoroacetic acid regulator (10 eq) were added to 12.5 mL of deionized water and stirred at room temperature for 30 min to obtain solution B. Subsequently, solution A and solution B were mixed and stirred at 60 °C for 24 h. After the reaction, the product was centrifuged, washed and dried in a vacuum oven at 120 °C for 18 h to prepare a UiO-66(Ce)-BDC-SO3 carrier with small size defects, recorded as U(Ce)-SO3-10eq. Then, 50 mg U(Ce)-SO3-10eq carrier was uniformly dispersed in 10 mL methanol solution at 40 °C, and 2 mL of freshly prepared nickel nitrate methanol solution (1 g / L Ni2+) was added. After the mixed solution was stirred for 8 h, 4 ml of freshly prepared methanol solution containing 25.78 mg sodium borohydride was added. The molar ratio of metal ions in the methanol solution of sodium borohydride and nickel nitrate was about 20:1. The reaction was stirred at 40 °C for 2 h. After centrifugation, washing, and vacuum drying at 80 °C for 10 h, the product was obtained. Small-size defect U(Ce)-SO3-10eq loaded with 4 wt% Ni nanoparticles composite catalytic material, recorded as Ni4@U(Ce)-SO3-10eq, was obtained.

[0041] DCPD hydrogenation performance and cycle stability test: 0.01 g of powdered catalyst was weighed and added to a high-pressure hydrogenation reactor, 5 mL of methanol solvent and 100 μL of DCPD substrate were added, the reactor was sealed, and the entire device was repeatedly purged with H2 to remove air. Then, the reactor H2 reaction pressure was set to 2 MPa, the reaction temperature was 70 ℃, the reaction time was 90 min, and the stirring speed was 600 rpm. After the catalytic reaction was completed, the catalyst and solvent were centrifuged and separated. The supernatant was diluted with methanol solvent and the product components were analyzed by GC-MS liquid chromatography-mass spectrometry. The DCPD conversion rate was 100% and the THDCPD selectivity was 95.45%. The centrifuged catalyst was centrifuged and washed 3 times with methanol and then transferred to a high-pressure hydrogenation reactor. The above steps were repeated. After 5 catalytic cycle tests, the DCPD conversion rate was 96.73% and the THDCPD selectivity was 90.66%.

[0042] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the thinking and principle of the present application should be included within the scope of the claims of the present application.

Claims

1. A method for preparing a small-size defect cerium-based MOFs-supported metal catalyst for hydrogenation, characterized in that: The specific preparation steps are: 1) preparing a mixed solution of an organic ligand, a soluble cerium salt, and a monocarboxylic acid regulator, reacting the mixture by a solvothermal method, centrifuging, washing, and drying the obtained product, and synthesizing a cerium-based MOFs carrier with adjustable defect content and size, wherein the molar ratio of the cerium salt to the monocarboxylic acid regulator in the mixed solution is 1:0.01-100; 2) Prepare a metal salt solution with a metal ion concentration of 0.01-10 g / L at room temperature; first, uniformly disperse the cerium-based MOFs carrier in a solvent at 25-100 °C, wherein the content of the cerium-based MOFs carrier in the solvent is 0.1-500 g / L, and add the prepared metal salt solution under stirring conditions to obtain a mixed solution, so as to promote the adsorption of metal ions into the cerium-based MOFs carrier framework, and the metal loading amount relative to the carrier is 0.01-20 wt%; 3) Adding the reducing agent solution to the mixed solution of step 2), the molar ratio of the reducing agent added to the metal ions in the added metal salt solution is 50~0.1:1, stirring the reaction at 25~100°C for 1~48 hours, and then centrifuging, washing and drying the product in sequence to obtain a cerium-based MOFs-loaded metal nanoparticle composite catalyst with adjustable size and defects.

2. The preparation method according to claim 1, characterized in that: The solvothermal method described in step 1) is to add an organic ligand to N,N-dimethylformamide (DMF) with a ligand solution concentration of 0.01-1 mol / L, stir at room temperature to completely dissolve the organic ligand to obtain a clear solution A; add a cerium salt and a certain amount of a monocarboxylic acid regulator to deionized water, stir at room temperature to mix the solution evenly, and obtain a clear and transparent solution B; mix solution A and solution B at a volume ratio of 0.01-1:0.01-1, and stir and react at 25-150 °C for 15 min-72 h.

3. The preparation method according to claim 1, characterized in that: The cerium salt described in step 1) includes one of ammonium cerium nitrate and cerium nitrate.

4. The preparation method according to claim 1, characterized in that: The monocarboxylic acid regulator described in step 1) includes one of formic acid, acetic acid, trifluoroacetic acid, benzoic acid, butyric acid, caprylic acid, capric acid, and lauric acid; the organic ligand described in step 1) includes one of terephthalic acid, 2-aminoterephthalic acid, 2-nitroterephthalic acid, 2-bromoterephthalic acid, 2-fluoroterephthalic acid, 2-sulfonic terephthalic acid, 2-hydroxyterephthalic acid, 2,5-dihydroxyterephthalic acid, 2,5-dichlorodiphenylmethane, 2,5-pyrazinedicarboxylic acid, 2,5-pyridinedicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, 2,2'-bipyridine-5,5'-dicarboxylic acid, and trimesic acid. ; The metal salt described in step 2) includes one of nickel nitrate, cobalt nitrate, copper nitrate, iron nitrate, zinc nitrate, platinum nitrate, palladium nitrate, nickel chloride, cobalt chloride, copper chloride, iron chloride, zinc chloride, ruthenium chloride, platinum chloride, and palladium chloride; the solvent of the metal salt solution described in step 2) includes one of deionized water, methanol, and ethanol; the solvent for dispersing the carrier described in step 2) includes one of deionized water, deionized water+n-hexane, methanol, and ethanol; the reducing agent described in step 3) includes one of sodium borohydride, tetrabutylamine borane, and hydrazine hydrate; the solvent for dissolving the reducing agent described in step 3) includes one of deionized water, methanol, and ethanol.

5. The preparation method according to claim 1 or 4, characterized in that: The monocarboxylic acid regulator described in step 1) is formic acid; the organic ligand described in step 1) is terephthalic acid; the metal salt described in step 2) is nickel nitrate; the solvent of the metal salt solution described in step 2) is methanol; the solvent for dispersing the carrier described in step 2) is methanol; the reducing agent described in step 3) is sodium borohydride; and the solvent for dissolving the reducing agent described in step 3) is methanol.

6. The preparation method according to claim 2, characterized in that: The stirring time at room temperature in step 1) is 5 min to 1 h.

7. The preparation method according to claim 1, characterized in that: Step 2) The stirring time is 1 to 48 h.

8. The preparation method according to claim 1, characterized in that: The reducing agent solution concentration in step 3) is 0.01-10 mol / L.

9. The preparation method according to claim 1, characterized in that: The drying described in step 1) and step 3) is performed by placing the mixture in a vacuum oven at 60-150° C. for 4-48 hours.

Citation Information

Cited By

  • Catalyst for ethylene glycol antimony and preparation process of ethylene glycol antimony

    CN119798041A

  • Preparation method and application of cerium-based metal organic framework photoelectric catalyst

    CN120060900A

  • MOF-based material with mimic enzyme activity as well as preparation method and application of MOF-based material

    CN120289821A

  • Synthesis method of N-hydroxymethyl phthalimide

    CN121005649A